Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Akuntansi Akrual Pada Pemerintah (Studi Kasus Pada Kementerian Sekretariat Negara) - Rendra Safa’at; Lawe Anasta (Jurnal Pena-Mas Akuntansi, 2020)
This study aims to determine the factors that affect the application of accrual accounting to the government. The data used are primary data obtained from the dissemination to 40 respondents. The method used to analyze the relationship and its effect is the method of multiple correlation analysis and t by using SPSS version 23. The results of this study indicate that in terms of personal, the variable level of the competency level, the experience of running the cash base toward accrual, the quality of information technology, the training of financial staff influences the application of accrual basis accounting at the state secretariat ministry. This is evidenced by the result (t-test) shows the significant value of the independent variable. Therefore, the test results of this study state that there is an influence between the variables of accrual basis accounting application at the state secretariat ministry.